Development of Android-Based Interactive Learning Media with STEM Nuances to Improve Creative Thinking Skills of Grade VIII Students - Hidayah, Fatimah Nurul; Sutarto, Hery (Unnes Journal of Mathematics Education, 2023)
This research aims to develop android-based interactive learning media with STEM nuances to improve students' creative thinking skills that are feasible and effective. The learning media was developed using iSpring software. This software is integrated with Microsoft Powerpoint which can make the learning media more interactive. The final form of learning media is an android application. The learning media is given STEM nuances and activities to facilitate students' creative thinking skills. STEM is a learning approach that connects science, technology, engineering, and mathematics. The indicators of creative thinking skills used are fluency, flexibility, originality, and elaboration. The development model used in this research is 4D (Define, Design, Development, Disseminate), but only up to the development stage. This research produces android-based interactive learning media with STEM nuances to improve the creative thinking skills of junior high school students in grade VIII that are feasible and effective. Media and material validation respectively obtained a score of 91.5% and 91.2% which included a very feasible category. The effectiveness of the media is shown in the improvement of students' creative thinking skills. The N-Gain test obtained shows that the increase in students' abilities has increased which is classified as moderate.